Comparative analysis of methods for determining total acid number in oil and derivatives from a sustainability perspective - Mendonça Ambrozim, Flaviane; Vieira, Raquel; Venial, Lucimara; Zanelato, Luana; Vicente, Maristela; Santos, Maria de Fátima (Latin American Journal of Energy Research, 2025)
The Total Acidity Number (TAN) is a critical parameter in the evaluation of the quality of petroleum and derivatives, influencing refining processes, equipment corrosivity and maintenance costs. Traditionally, classical colorimetric, potentiometric, and thermometric methods, such as ASTM D974, ASTM D664, and ABNT NBR 14448, have been widely used due to their simplicity and reliability. However, these methods have high consumption of organic solvents and waste generation, as well as limitations regarding accuracy in complex matrices. Thus, the objective of this work was to comparatively analyze the main methods of determining TAN in petroleum and derivatives, considering analytical efficiency and sustainability criteria, through the Sustainability Degree Assessment (GS). A systematic survey was carried out (Scielo, Web of Science, Scopus and Google Scholar) and sustainability was evaluated by Multicriteria Analysis (MCDA) in three criteria: Environmental (weight 0.5), Economic (0.3) and Social/Operational (0.2) with a score from 1 to 5. The SG was calculated by weighted average and classified as low (GS<2.0), medium (2.0≤GS<3.5) and high (GS≥3.5). The results showed that the colorimetric methods have low sustainability (SG between 2.85 and 3.25), while the classical potentiometric methods have medium sustainability (SG between 2.65 and 3.05). The Micellar Solubilization Nanoemulsion (MSN) method stood out as a promising alternative, reaching GS=3.60 and being classified as highly sustainable. The ASTM D8045 thermometric method obtained GS=3.30, configuring itself as an intermediate technology. It was concluded, therefore, that the colorimetric methods presented lower sustainability (high use of solvents and subjectivity), while the classical potentiometric methods had intermediate performance, with the MSN method being the most sustainable and robust, while the thermometric method is the intermediate.